2019
DOI: 10.3390/molecules24081573
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Different Blossom Honeys: New Findings

Abstract: Antibacterial activity is the most investigated biological property of honey. The goal of this study was to evaluate the antibacterial activity of 57 Slovak blossom honeys against Staphylococcus aureus and Pseudomonas aeruginosa and investigate the role of several bioactive substances in antibacterial action of honeys. Inhibitory and bactericidal activities of honeys were studied to determine the minimum inhibitory and bactericidal concentrations. The contents of glucose oxidase (GOX) enzyme, hydrogen peroxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 51 publications
(61 reference statements)
8
123
1
1
Order By: Relevance
“…The antibacterial activity of manuka and kanuka honeys are mainly mediated by highly reactive methylglyoxal [9][10][11]. Blossom honeys such as acacia, rapeseed, linden, and sunflower, together with honeydew honeys, exhibit antibacterial activities mainly mediated by the presence of hydrogen peroxide (H 2 O 2 ) [12,13]. Indeed, H 2 O 2 was shown to be a major antibacterial compound of natural honey.…”
Section: Of 13mentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial activity of manuka and kanuka honeys are mainly mediated by highly reactive methylglyoxal [9][10][11]. Blossom honeys such as acacia, rapeseed, linden, and sunflower, together with honeydew honeys, exhibit antibacterial activities mainly mediated by the presence of hydrogen peroxide (H 2 O 2 ) [12,13]. Indeed, H 2 O 2 was shown to be a major antibacterial compound of natural honey.…”
Section: Of 13mentioning
confidence: 99%
“…The antibacterial efficacies of the honey samples were evaluated with a MIC assay, as described by Bucekova et al (2019) [13]. First, an overnight bacterial culture was suspended in phosphate-buffered saline (PBS) (pH 7.2), and the turbidity of the suspension was adjusted to 10 8 colony-forming units (CFU) per milliliter and diluted with Muller-Hinton medium (MHB) to a final concentration of 10 6 CFU/mL.…”
Section: Determination Of the Antibacterial Activities Of Honey Vitamentioning
confidence: 99%
“…Glucose oxidase (GOX) is an enzyme that mediates conversion of glucose to H 2 O 2 and gluconic acid under aerobic conditions in diluted honey . It is secreted from bee hypopharyngeal glands into the processed nectar and it is a regular but quantitatively variable compound of each honey sample …”
Section: Introductionmentioning
confidence: 99%
“…Also, Flanjak et al [14] observed the mean of glucose oxidase of 45 studied honey samples as 40.3-347.6 μg H 2 O 2 /h·g. According to another study, the average value of 57 blossom honey samples tagged as acacia (n � 15), wildflower (n � 32), and rapeseed (n � 8) were found as 29.7 μg/g [22]. When comparing relevant results, it was surprising that our initial values were quite low.…”
Section: Glucose Oxidase Values Of Honey Samplesmentioning
confidence: 65%